(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article is about the issue of developing the linguistic competence of primary school students in terms of adjective vocabulary in their native language classes, as well as the methods used to form linguistic competence in the adjective vocabulary of primary school students. provides theoretical information and analyzes these methods.